Type synthesis of a class of novel 3-DOF single-loop parallel leg mechanisms for walking robots. (March 2020) - Li, Luquan; Fang, Yuefa; Guo, Sheng; Qu, Haibo; Wang, Lin
Highlights: An approach for constructing the 3-DOF single-loop parallel leg mechanism is proposed. Equivalent drive mechanisms are presented to substitute the serial chains with two serial actuated joints. A novel class of 3-DOF single-loop parallel leg mechanisms with 3T/1R2T/2R1T motions are constructed. The performances are analyzed to show that the novel leg mechanisms possess more advantages. The simulation is provided to illustrate the omnidirectional walk of quadruped robot. Abstract: This paper presents a class of novel 3-degree-of-freedom (DOF) single-loop parallel leg mechanisms for walking robots. An approach for constructing the 3-DOF single-loop parallel leg mechanism is proposed. The single-loop parallel leg mechanism is composed of a serial limb with two actuated joints and a serial limb with one actuated joint, where two serial actuated joints of a limb are replaced by an equivalent drive mechanism. The novel legs can generate three translation (3 T ), two rotation and one translation (2 R 1 T ), and one rotation and two translation (1 R 2 T ) motions, which make the workspace of the foot-endpoint three-dimensional in volume, and the robots can walk flexibly and omnidirectionally. Compared with existing leg mechanisms, the novel leg mechanisms have the potential advantages of larger step length and step height. This will enable the walking robot to move faster and step over larger obstacles. A quadruped robot is built with novel leg mechanisms, and its performances are analyzed and omnidirectional walk is demonstrated by simulation.